The effect of sacubitril/valsartan on urinary C-peptide excretion and endogenous insulin secretory capacity in a patient with type 2 diabetes: a case report - Shun Onodera; Masashi Miyamae; Issei Higuchi; Shunsuke Nashimoto; Akinobu Nakamura; Mitsuru Sugawara; Yoh Takekuma (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background The evaluation of endogenous insulin secretory capacity is important in the selection of diabetes treatment. C-peptide, which is secreted in equivalent amounts as insulin, is a versatile test for this evaluation. Urinary C-peptide is widely used because it is less invasive. Sacubitril/valsartan, used to treat hypertension and chronic heart failure, has been reported to increase urinary C-peptide levels; however, its effect on endogenous insulin secretion remains unknown. In this report, we present a case in which insulin secretory capacity was evaluated according to a glucagon stimulation test in addition to urinary C-peptide levels in a patient receiving sacubitril/valsartan. Case presentation A male patient in his 50s with type 2 diabetes and hypertension, without renal dysfunction, was treated with sacubitril/valsartan. The results of the glucagon stimulation test showed a C-peptide change of 2.28, and the C-peptide index on the same day was 1.25, indicating normal endogenous insulin secretory capacity. In contrast, 24-h urinary C-peptide excretion was abnormally high at 615.2 µg/day. After discontinuation of sacubitril/valsartan, urinary C-peptide excretion decreased over time (615.2 to 369.0 µg/day), but blood glucose levels did not increase during this period. Conclusions In this case, 24-h urinary C-peptide excretion was abnormally elevated despite preserved endogenous insulin secretory capacity, as assessed by the glucagon stimulation test. Although this observation is based on a single case and cannot be generalized, it suggests that sacubitril/valsartan may interfere with the interpretation of urinary C-peptide levels. Therefore, in such clinical contexts, dynamic tests such as the glucagon stimulation test may serve as a useful adjunct to avoid potential overestimation of insulin secretory capacity when relying solely on urinary C-peptide levels.